Tafsir and Local Interpretation Analysis:: Study of Muqatha’ah Letters in the Qur'an through the Perspective of K.H. Bisri Mustofa - Dwi Nugraha, Arnawan (Journal of Ulumul Qur'an and Tafsir Studies, 2024)
This article discusses the interpretation of K.H. Bisri Mustofa regarding the Muqatha’ah letters in the Qur'an. The localization of Javanese-language tafsir books and the nuances of Nusantara interpretation underscore the significance of studying this topic. This study uses a quantitative study method with a literature review approach. The data sources are the book "Tafsir al-Ibriz". Data collection techniques using search methods and data analysis techniques using content analysis. This article finds that the Muqatha’ah letters (al-ahruf al-muqatha’ah) entail diverse interpretations and spark debates among scholars of tafsir. This study offers insights into the complexity of interpreting the Muqatha’ah letters and highlights the differing opinions among scholars, while integrating local perspectives into the study of Qur'anic exegesis.